Landscape architectural proposal of the leisure path along the river Gauja in latvia - Bihuňová , M.; Bremane, A. (Man and Environment. Issues of Neoecology, 2025)
Purpose. To propose the recreational educational trail for the public along the river Gauja. Methods. Field, landscape and architectural proposal. Results. The recreational educational trail will lead along riverside and has a start point at an active leisure park ‘’Rāmkalni’’, about 40 km away from the capital of Latvia- Riga and end in Sigulda, about 53 km away from Riga. The planned route includes 8 stops who are currently separated and don’t have a connecting route yet. For the trails and stairs in places of terrain changes, it is planned to use the wood of Larix trees, as it rots much more slowly than other trees. The topics of the informational boards in the planned trail are educational about: the trail, Gauja River, Gauja National park, geology of the cliffs, active leisure park ‘’Tarzāns’’, Sigulda city. Conclusions. The landscape architectural proposal and design of the equipment is simple, minimalistic and natural shapes, with simple bench and information sign structures, mostly using wood material like wooden beams. Most of the places showcase the beauty of the picturesque Gauja Valley, some of them are also designed for outdoor activities